The Thermodynamic Stability, Electronic and Photocatalytic Properties of the ZnWO(4)(100) Surface as Predicted by Screened Hybrid Density Functional Theory - Wu, Yonggang (ACS Omega, 2021)
[Image: see text] Zinc tungstate (ZnWO(4)) is an outstanding photocatalyst for water splitting and organic contaminant degradation under visible light irradiation. Surface termination stabilities are significant for understanding the photochemical oxidation and reactions on the ZnWO(4) surface. Based on density functional theory, we calculated the thermodynamic stability of possible surface terminations for ZnWO(4)(100). The surface stability phase diagrams show that the Zn(2)O(4)-Zn(8)W(6)O(28), W(2)O(4)-Zn(8)W(10)O(36), and Zn(2)-Zn(8)W(6)O(24) terminations of ZnWO(4)(100) can be stabilized under certain thermodynamic equilibrium conditions. The electronic structures for these three possible stability surface terminations are calculated based on the Heyd–Scuseria–Ernzerhof (HSE06) hybrid functional to give dependable theoretical band gap values. It is found that the surface states of W(2)O(4)-Zn(8)W(10)O(36) termination are in the band gap, which shows a delocalized performance. The calculated absorption coefficients of W(2)O(4)-Zn(8)W(10)O(36) termination show stronger absorption than bulk ZnWO(4) in the visible-light region. The band edge calculation shows that the valence band maximum and conduction band minimum of the W(2)O(4)-Zn(8)W(10)O(36) termination can fulfill the hydrogen evolution reaction and oxygen evolution reaction requirements at the same time. Furthermore, work functions are extraordinarily distinct for various surface terminations. This result suggests that the ZnWO(4)-based direct Z-scheme heterostructure can be controlled by obtaining the thermodynamically preferred surface termination under suitable conditions. Our results can predict ZnWO(4)(100) surface structures and properties under the entire range of accessible environmental conditions.